Exploring the modulation of MLH1 and MSH2 gene expression in hesperetin-treated breast cancer cells (BT-474) - Ahmed Mohammed Salman; Esmaeil Babaei; Ahmed Salim Kadhim Al-Khafaji (Wolters Kluwer Medknow Publications, 2024)
The major mortality factor for women globally is breast cancer, and current treatments have several adverse effects. Hesperetin (HSP) is a flavone that occurs naturally with anti-tumor capabilities and has been investigated as a potential treatment for cancer. This study aimed to investigate the cytotoxic and anti-malignant potential of HSP on breast cancer cells (BT-474) and normal cells (MCF-10a). The results indicated that HSP has dose-dependent cytotoxicity in BT-474 and MCF-10a cells. The elevated concentration of HSP lowered cell viability and proliferation. The half-maximal inhibitory concentration (IC50) of HSP in BT-474 cancer cells after a 48-h exposure was 279.2 μM/ml, while the IC50 in normal cells was 855.4 μM/ml. The cytotoxicity of HSP was more significant in cancer cell lines than in normal cell lines and this aspect presents a favorable factor in utilizing the drug for the treatment of breast cancer. The apoptotic effect of HSP in BT-474 cells was investigated, and it was found that the higher the concentration of HSP more the cells underwent apoptosis. Furthermore, the highest concentration of HSP led to overexpression of the MLH1 and MSH2 genes in both breast cancer and normal cell lines. Overall, our study suggests that HSP has an anticancer effect on breast cancer cell lines, and the effect is concentration dependent.